Primary Central Nervous System Extranodal NK/T Cell Lymphoma, Nasal Type, with Antecedent Hemophagocytic Syndrome in a Child. (November 2014) - Jiang, Xianping; Yin, Weihua; Song, Jianming; Chen, Xiaowen; Zhao, Cailei; Wen, Feiqiu
Primary central nervous system (CNS) extranodal natural killer (NK)/T-cell lymphoma, nasal type (NKTCL), is an exceedingly uncommon entity. Here, we present a case of CNS NKTCL that manifested initially as hemophagocytic syndrome 4 months earlier in a 13-year-old girl. Histological examination revealed the cerebellum mass was composed of large-sized and atypical tumor cells, with an angiocentric and angiodestructive growth pattern and prominent necrosis. The tumor cells exhibited marked pleomorphism with conspicuous nucleoli and prominent mitotic activity. Immunohistochemical staining showed the tumor cells were positive for CD45, CD2, CD3ε, CD30, CD43, CD56, and granzyme B. Epstein-Barr virus––encoded ribonucleic acid was expressed in almost all of the nuclei of the lymphoma cells. The T-cell receptor γ chain gene rearrangement study showed no evidence of a clonal rearrangement. The patient was treated with etoposide and dexamethasone and died a few days after the operation. As far as we know, this case is the 1st pediatric and female patient of primary CNS NKTCL with antecedent hemophagocytic syndrome, which highlights the clinical data and is helpful for the diagnosis of this tumor.